2016
DOI: 10.1007/s11661-015-3306-5
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Treatment Duration and Cooling Rate on Pure Aluminum Solidification Upon Pulse Magneto-Oscillation Treatment

Abstract: The effect of pulse magneto-oscillation (PMO) treatment on casting grain size has been widely investigated. Nevertheless, its mechanism remains unclear, especially when PMO is applied at different periods during solidification, namely when only applied above the melting point. In the present work, the effect of PMO treatment applied at different segments during solidification was investigated. It was found that the dendrite fragmentation model may well explain the effect of PMO applied during the dendrite grow… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
9
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(9 citation statements)
references
References 20 publications
0
9
0
Order By: Relevance
“…Consequently, slag control and surface examination are more difficult with PMO than that without. Our Previous simulation results showed that magnetic field induced by SPMO tended to cluster near the melt surface and along the mold wall, not at the center of the melt [24,27]. We deduced that if the coil could be given the form of a ring rather than a disc, slag control and surface examination would be much easier.…”
Section: Simplification Of Coil Configuration To Optimize Pmomentioning
confidence: 90%
See 1 more Smart Citation
“…Consequently, slag control and surface examination are more difficult with PMO than that without. Our Previous simulation results showed that magnetic field induced by SPMO tended to cluster near the melt surface and along the mold wall, not at the center of the melt [24,27]. We deduced that if the coil could be given the form of a ring rather than a disc, slag control and surface examination would be much easier.…”
Section: Simplification Of Coil Configuration To Optimize Pmomentioning
confidence: 90%
“…The main parameters of PMO, including the peak current, the frequency, and the configuration of the PMO coil, can all be easily adjusted and controlled. Refinement effect was better with higher peak current and lower frequency [19,[21][22][23][24][25][26]. PMO treatment shows great promise in the production of heavy steel ingots on an industrial scale [27].…”
Section: Introductionmentioning
confidence: 98%
“…Consequently, slag control and surface examination are more difficult with PMO than without. Our Previous simulation results showed that magnetic field induced by SPMO tended to cluster near the melt surface and along the mold wall, not at the center of the melt [24,28]. We deduced that if the coil could be given the form of a ring rather than a disc, slag control and surface examination would be much easier.…”
Section: Simplification Of Coil Configuration To Optimize Pmomentioning
confidence: 90%
“…Itzhak et al studied the effect of application of PMO at different stages of solidification and under different cooling rate on both the solidification structure and the recalescence temperature [15][16][17]. Sun et al [18] deduced that the convection in steel melt induced by PMO forced the grains to move from the solid-liquid interface, which resulted in the formation of uniformly distributed dendrites throughout the whole ingot.…”
Section: Introductionmentioning
confidence: 99%